Antifungal activity of peracetic acid against toxigenic fungal contaminants of maize and barley at the postharvest stage. (August 2021) - Luz, Carlos; Carbonell, Raquel; Quiles, Juan Manuel; Torrijos, Raquel; de Melo Nazareth, Tiago; Mañes, Jordi; Meca, Giuseppe
Abstract: Contamination of maize and barley grain during storage by the toxigenic fungi Aspergillus flavus ( A. flavus ) and Penicillium Verrucosum ( P. verrucosum ) is both an economic and a public health problem, especially in less industrialized countries. Peracetic acid (PA) is a compound used for the disinfection of food and food contact surfaces. Unlike other disinfectants, it leaves no toxic residues and its decomposition products (CH3 COOH, O2 and H2 O) are environmentally friendly. In order to apply PA to preserve maize and barley grain during storage, first, the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) against both fungi were determined in a 96-well sterile microplates. Then, the antifungal activity of the volatile PA was determined by depositing it on filter paper and Hydroxyethylcellulose (HEC) gels, which were placed in airtight 1L flasks together with PDA and maize and barley grain inoculated with both fungi. The MFC in liquid medium of A. flavus and P. verrucosum was 93.8 and 187.5 mg/L respectively. However, PA doses of 300 and 200 mg/L on HEC gels were required in order to observe significant antifungal and antimycotoxigenic activity in maize and barley grain inoculated with these fungi. Graphical abstract: Image 1 Highlights: Volatile peracetic acid presents antifungal activity against A. flavus and P. verrucosum. Hydroxyethylcellulose gels with 300 mg/L of peracetic acid preserve stored maize and barley grains. The mentioned gels inhibit the synthesis of aflatoxin B1 and ochratoxin A in stored grain.